Non-invasive tools for the diagnosis of cutaneous melanoma - Müller-Christmann, Christine; Hänßle, Holger (Skin research & technology, 2017)
Background While the excisional biopsy and histological examination of suspicious lesions remains the current gold standard for diagnosing cutaneous melanoma (CM), there is a demand for more objective and non-invasive examination methods that may support clinicians in their decision when to biopsy or not. Methods This review is based on publications and guidelines retrieved by a selective search in PubMed and MEDLINE and focused on non-invasive diagnostic strategies for detecting melanoma. Results Ten different non-invasive techniques were compared with regard to applicability, status of development, and resources necessary for introduction into clinical routine (dermoscopy, sequential digital dermoscopy, total body photography, computer-aided multispectral digital analysis, electrical impedance spectroscopy, Raman spectroscopy, reflectance confocal microscopy, multiphoton tomography, stepwise two-photon-laser spectroscopy, quantitative dynamic infrared imaging). In an effort to create a classification based on our analyses, we suggest to differentiate i) tools for screening of patients in daily clinical routine, ii) tools for examination of a restricted number of preselected lesions that produce an automated diagnostic score, iii) tools for examination of a restricted number of preselected lesions at specialized centers requiring extensive training, iv) devices at an experimental stage of development. Conclusion None of the discussed examination techniques is able to provide a definite and final diagnosis or to completely replace the histopathological examination. Up to date, the need for fully automated devices offering a complete skin cancer screening has not been satisfied.